Killer summer [large type] - Pearson, Ridley (Pearson, Ridley. Sun Valley., 2009)
Sun Valley sheriff Walt Fleming returns in this high-intensity thriller as he thwarts a plan to steal a rare wine at the annual wine auction. When a bomb detonates just as the auction revs up, the investigation explodes as well, pulling Walt in a dozen different directions.